Experimental determination of deformation homogeneity and shear states using the digital image correlation method. (April 2021) - Filho, J.C.A.D.; Nunes, L.C.S.
Abstract: One of the great challenges in the pure shear and simple shear tests is to maintain the deformation state and deformation homogeneity of a specimen under large deformations. For this reason, the aim of this work is to investigate the state of shear deformation and degree of deformation homogeneity of three different shear specimens. A simple and easily replicable methodology was proposed to estimate the degree of deformation homogeneity of specimens, while a time-independent kinematic vorticity parameter was employed to identify pure shear and simple shear deformation states. All data were obtained from full-field displacements that were extracted with the two-dimensional digital image correlation (2D-DIC) method. Specimens of polytetrafluoroethylene (PTFE) were tested using the modified slotted shear test and the V-notched rail shear test, which are used to induce a simple shear state. The planar tensile test was used to produce a pure shear state in a thin sheet of rubber-like material. For small deformations, both slotted and V-notched shear tests induced a good degree of deformation homogeneity along the shear path between the notches of specimens, mainly in the central region. However, the V-notched specimens buckled at large deformation, producing a decrease in the degree of deformation homogeneity. In this case, the results were qualitatively assessed due to the errors associated with out-of-plane motions. High degree of deformation homogeneity was also observed in pure shear specimens. All tests demonstrated to be effective for inducing a state of pure shear or simple shear. Results show that the two approaches can be used as supplementary tools for determining the state of shear deformation and degree of deformation homogeneity. Highlights: Modified slotted shear test and V-notched rail shear test were used to generate a simple shear state in PTFE specimens. Planar test was used to generate a pure shear state in a rubber-like material. Displacement and deformation fields were obtained using the 2D-DIC method. Two approaches were proposed to investigate the shear deformation states and degree of deformation homogeneity. Proposed approaches can be used as supplementary data to validate new shear devices for large deformations.